2020
DOI: 10.18231/j.ijcbr.2020.007
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements (Copper and Zinc) in type 2 DM patients

Abstract: As Diabetes Mellitus is a metabolic disorder, where metabolism of various trace elements is being altered. Present study has been carried out to find out the association between Diabetes Mellitus and alteration in the level of trace elements. To analyse the level of trace elements (Copper and Zinc) in type 2 DM patients in comparison with healthy controls. The present cross sectional study was carried out in 100 patients, having minimum five-year duration of Type 2 Diabetes Mellitus. The study was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Samadi et al [ 72 ] indicated that T2DM patients had 3-fold lower plasma Zn levels and significantly higher TG levels compared to controls [ 72 ]. Serum Zn levels were found to be significantly lower in T2DM patients compared with healthy controls [ 73 ]. Moreover, the current study demonstrated a significant positive correlation between serum Zn levels and TG and TyG.…”
Section: Discussionmentioning
confidence: 99%
“…Samadi et al [ 72 ] indicated that T2DM patients had 3-fold lower plasma Zn levels and significantly higher TG levels compared to controls [ 72 ]. Serum Zn levels were found to be significantly lower in T2DM patients compared with healthy controls [ 73 ]. Moreover, the current study demonstrated a significant positive correlation between serum Zn levels and TG and TyG.…”
Section: Discussionmentioning
confidence: 99%